Congruences involving F-partition functions - James Sellers (International Journal of Mathematics and Mathematical Sciences)
The primary goal of this note is to prove the congruence ϕ3(3n+2)≡0(mod3), where ϕ3(n) denotes the number of F-partitions of n with at most 3 repetitions. Secondarily, we conjecture a new family of congruences involving cϕ2(n), the number of F-partitions of n with 2 colors.